Optimizing Financial Inclusion through Mobile Banking and Digital Wallet during COVID-19 Pandemic - Makusara, Kumaralalita; Widiastuti, Cahyaning Ajeng; Pangestuti, Irene Rini Demi; Mawardi, Wisnu (Economic and Business Horizon, 2025)
The COVID-19 pandemic has greatly affected multiple sectors in Indonesia, particularly the financial sector. Amidst economic uncertainty, financial inclusion is crucial to support economic recovery and community welfare. Mobile banking and digital wallets have emerged as effective solutions in improving financial inclusion, facilitating wider access to financial services for people, especially in remote areas. This research uses the journal review method, by analyzing various research sources related to the role of mobile banking and digital wallets in improving financial inclusion in Indonesia during the pandemic. The findings show that digital financial technology has accelerated the process of financial inclusion, with positive impacts on economic sustainability. By enabling easier and safer access to finance, mobile banking and digital wallets support the achievement of sustainability goals through reducing social and economic inequality. This research contributes to a better understanding of the potential of digital technology in supporting sustainable financial inclusion, and its implications for public policy in Indonesia.